2022
DOI: 10.1093/brain/awac105
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the relationship between migraine risk and brain structure using genetic data

Abstract: Migraine is a highly common and debilitating disorder that often affects individuals in their most productive years of life. Previous studies have identified both genetic variants and brain morphometry differences associated with migraine risk. However, the relationship between migraine and brain morphometry has not been examined on a genetic level, and the causal nature of the association between brain structure and migraine risk has not been determined. Using the largest available genome-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 77 publications
1
9
1
Order By: Relevance
“…In addition, we used wellpowered GWAS data of migraine, which had more statistical power to detect associations than past smaller study. Finally, our results were in lined with a recent MR study based on voxel-based morphometry, which additionally increased the robustness of our results (Mitchell et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, we used wellpowered GWAS data of migraine, which had more statistical power to detect associations than past smaller study. Finally, our results were in lined with a recent MR study based on voxel-based morphometry, which additionally increased the robustness of our results (Mitchell et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, observational evidence showed that HV had been negatively associated with the frequency and severity of migraine attacks (Maleki et al, 2013;Liu et al, 2017). Mitchell et al (2022) suggested that migraine attacks might influence HV in a longitudinal study. However, this reverse relationship was not verified in our study or a recent MR study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GWAS-pairwise (GWAS-PW) method 77 was used to identify specific segments of the genome influencing PD and at least one of the eight brain structures with a statistically significant genetic correlation, as described previously 78 . We conducted GWAS-PW analyses for PD and each of the eight brain structures, separately.…”
Section: Methodsmentioning
confidence: 99%
“…Large-scale genome-wide association studies (GWAS) on both brain imaging-derived phenotypes (IDPs) and neuropsychiatric disorders provide opportunities to explore the causality between exposure (e.g., brain IDPs) and outcome (e.g., diseases) [ 17 ]. Using MR, a recent study explored the causal effects of subcortical regions and intracranial volume (ICV) on migraine [ 18 ]. MR results demonstrated a possible causal relationship between smaller ICV, hippocampal and ventral diencephalon volume and increased migraine risk, while reverse MR showed causality between increased migraine risk and a larger volume of the amygdala.…”
Section: Introductionmentioning
confidence: 99%